2016
DOI: 10.1038/tp.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity-based thrifty eating phenotype and the protective role of n-3 PUFAs intake in adolescents

Abstract: The goal of the present study was to investigate whether intrauterine growth restriction (IUGR) affects brain responses to palatable foods and whether docosahexaenoic acid (DHA, an omega-3 fatty acid that is a primary structural component of the human brain) serum levels moderate the association between IUGR and brain and behavioral responses to palatable foods. Brain responses to palatable foods were investigated using a functional magnetic resonance imaging task in which participants were shown palatable foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…The observed associations between lower BWz and greater eating in the absence of hunger among girls are consistent with prior evidence that IUGR and LBW are associated with greater external and restrained eating, neuronal response to viewing of palatable foods in children, objectively assessed impulsive eating in girls, and sweet taste preference . This study contributes to this growing but still small body of evidence by demonstrating associations between lower birthweight and an objective measure of appetite regulation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The observed associations between lower BWz and greater eating in the absence of hunger among girls are consistent with prior evidence that IUGR and LBW are associated with greater external and restrained eating, neuronal response to viewing of palatable foods in children, objectively assessed impulsive eating in girls, and sweet taste preference . This study contributes to this growing but still small body of evidence by demonstrating associations between lower birthweight and an objective measure of appetite regulation.…”
Section: Discussionsupporting
confidence: 87%
“…Our study adds to the extant literature regarding birthweight and child appetite regulation by providing some of the first evidence for associations across the full spectrum of birthweight and child eating behaviour, including large birth size (LGA or high birthweight), which is strongly associated with later obesity . A small number of studies examine birthweight as a continuous variable, finding less picky eating and less neuronal response to food with increasing birthweight . Yet, consideration of only linear associations may distort associations by precluding identification of adverse outcomes at both the lower and higher ends of the spectrum of birth size.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…55 The supplementation with n-3 polyunsaturated fats directly to the offspring exposed to prenatal adversity also seems to be associated with less brain oxidative damage in rodents. 58 Infants born to mothers who report high prenatal stress and low partner support exhibit higher cortisol reactivity relative to those whose mothers report high support, suggesting that partner support may buffer the impact of prenatal stress on infant cortisol reactivity. For instance, we have shown that children exposed to poor fetal growth have better inhibitory control when consuming n-3 polyunsaturated fats, 57 reflected in patterns of prefrontal cortex activation in functional MRI in adolescents.…”
Section: Possible Factors For Reversibilitymentioning
confidence: 99%